The relationship between alienation and education in research on Education Policy: meta-research contributions (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
Based on the dialectical historical materialism, this text presents some results of a broader study addressing the problem of alienation in research on Education in Brazil, mainly regarding Education Policies, seeking to advance, at this moment, in explaining the use of meta-research as a methodological procedure and its importance for the development and improvement of scientific production, since all scientific knowledge can only go forward considering the contributions of the previously systematized production. The research data collection was carried out by surveying the catalogue of theses and dissertations of the Brazilian Coordination for the Improvement of Higher Education Personnel (CAPES), focusing on the material produced between 2008 and 2018. In total, 198 papers were analyzed, 46 of which were research lines on Education Policy. The research results indicate that the number of studies addressing the relation between alienation and education, inserted in Education Graduate Programs and research lines or study areas is very low, while the implications for education of the alienation intensification in current society show the need for research on Education, mainly on Education Policy, to advance in studies about alienation.Keywords: Meta-research. Alienation. Education. Education Policy.